Diseleno[3, 2‐b:2′, 3′‐d]selenophene‐Containing High‐Mobility Conjugated Polymer for Organic Field‐Effect Transistors. Issue 13 (26th April 2019) - Jang, Soo‐Young; Kim, In‐Bok; Kang, Minji; Fei, Zuping; Jung, Eunhwan; McCarthy‐Ward, Thomas; Shaw, Jessica; Lim, Dae‐Hee; Kim, Yeon‐Ju; Mathur, Sanjay; Heeney, Martin; Kim, Dong‐Yu
Abstract: The synthesis of a diseleno[3, 2‐ b :2′, 3′‐ d ]selenophene (DSS) composed of three fused selenophenes is reported and it is used as a building block for the preparation of a high hole mobility conjugated polymer (PDSSTV). The polymer demonstrates strong intermolecular interactions even in solution, despite steric repulsion between the large Se atom in DSS and adjacent (Cβ )–H atoms which leads to a partially twisted confirmation PDSSTV. Nevertheless, 2D grazing incidence X‐ray diffraction (2D‐GIXD) analysis reveals that the polymer tends to align in a highly ordered edge‐on orientation after thermal annealing. The polymer demonstrates promising performance in a field‐effect transistor device with saturated hole mobility up to 2 cm 2 V −1 s −1 obtained under relatively low gate voltages of −30 V. The ultilization of a Se‐containing fused aromatic system, therefore, appears to be a promising avenue for the development of high‐performance conjugated polymers. Abstract : A high mobility conjugated polymer, PDSSTV, is synthesized using newly developed diseleno[3, 2‐ b :2′, 3′‐ d ]‐d]selenophene (DSS). Due to large and polarizable orbitals of selenium in DSS, the polymer demonstrates strongly aggregated property with high crystallinity after thermal annealing, even though it shows nonplanar backbone structure. At ‐30 V, a maximum mobility of 2.1 cm 2 V −1 s −1 is achieved with gate voltage independent behavior.